Biobased epoxy thermosets from vanillin-derived oligomers. (July 2015) - Fache, Maxence; Viola, Arnaud; Auvergne, Rémi; Boutevin, Bernard; Caillol, Sylvain
Graphical abstract: Highlights: Vanillin-based epoxy oligomers were prepared by adapting an existing industrial process used for bisphenol A-based resins. Chain length was controllable through reactant stoichiometry as predicted by Carothers' equation. Tg of the oligomers increased with chain length, following the Flory–Fox model. Biobased epoxy thermosets from these vanillin-derived oligomers displayed excellent thermo-mechanical properties. Materials properties were tunable with chain length of the oligomers used. Abstract: Novel vanillin-derived epoxy oligomers were prepared and crosslinked to yield biobased epoxy thermosets. This work directly continues the efforts engaged by our team to use vanillin as a renewable building block for polymer chemistry as it is an industrially available, non-toxic, wood-derived compound. The oligomers were synthesized by adapting and optimizing an industrial strategy currently in use, consisting in the chain-extension of a diepoxy monomer in excess by the poly(addition) of a diphenol. The length of the oligomers prepared was controlled by the stoichiometry of the reactants, and well-predicted by Carothers' equation. A 1 H NMR titration method was implemented to determine the epoxide indexes of the oligomers, which were very close to the ones calculated. The thermal properties of the oligomers were investigated and their Tg increased with the chain length, in accordance with the Flory–Fox equation. Thermosets were prepared by crosslinking these biobased epoxy oligomers with a common industrial amine hardener. The materials obtained displayed good thermo-mechanical properties that were tunable with the chain length of the oligomer employed. The current strategy used in industry was found to be applicable to renewable resources-based epoxy resins.